Resilience of Islamic Banking in Indonesia: A VECM Analysis of Macroeconomic Shocks and Medium-Term Recovery Dynamics - Fariza Bahari Fadliani; Muhammad Muflih; Iwan Setiawan; Dwi Suhartanto; Moch. Edman Syarief (International Journal of Islamic Economics and Governance, 2025)
The failure of conventional economics during the 2007/2008 crisis spurred the emergence of Islamic economic alternatives this day. Comparative studies have assessed its resilience. This research comprehensively examines Islamic banking’s resilience to economic crises, addressing gaps in previous studies that focused only on specific crisis periods. Monthly data from 2015-2023 from SPS- OJK, BPS, and Monetary Statistics-BI were analyzed using VECM methods. Real GDP was found to have the most significant negative impact on various Indonesian Islamic banking performance variables. Islamic banks can, therefore, utilize an Early Warning System for real GDP. The variables affected by macroeconomic shocks show short- to medium-term dynamics, recovering from periods 3-5, and stabilizing performance. This study fills previous research gaps that indicated instability in Islamic banking by considering only short post-crisis periods. In the medium term, Islamic banking in Indonesia has proven effective in recovering from crises, as shown by the analysis of recurring economic crises. © 2025 The Author(s). Licensed under CC BY-NC 4.0.